Naqd Al-Nassh Lil Qur'an: Study of Reason Criticism of the Qur'an According to Ali Harb - Teuku Muhammad Fauzan Robbani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article aims to explore Ali Harb's thoughts on the concept of Naqd al-Nassh (Textual Criticism) in Qur'anic studies. As a contemporary Lebanese intellectual deeply influenced by the post-structuralist tradition, Ali Harb offers a new perspective that goes beyond classical methods of exegesis. Through a library study of relevant journals, this research outlines how Ali Harb deconstructs text authority and religious reason considered to be frozen. The research results show that Ali Harb's version of the critique of Qur'anic reason does not aim to undermine the sanctity of the text, but rather to dismantle the thought mechanisms (epistemology) of Muslims in understanding the text so that it remains productive and relevant to contemporary reality. Ali Harb encourages a shift from